Evaluation of serum soluble E-selectin in breast cancer - Halla Mohamed Ragab, Mie Afify, Nervana Samy, Nabila Abd El Maksoud, HebatAllah Mohamed Shaaban (Journal of Applied Pharmaceutical Science, 2017)
Breast cancer is a highly metastatic disease even after surgical removal of the primary tumor. Metastasis is the main cause of death in breast cancer patients. The aim of the study was to assess the concentration of E-selectin in serum and tissue from breast cancer patients and women suffering from benign breast disease to determine its prognostic value in these diseases. This study was conducted on three groups of patients: Group A included 92 breast cancer patients, Group B included 25 patients with benign breast and group C (the control group) included 16 subjects. Blood samples were withdrawn for the estimation of serum E-selectin by ELISA and the gene expression of E-selectin was examined in Breast tissue samples. The results showed that serum level of E-selectin was highly significantly increased in malignant group as compared to benign and control groups (P < 0.05), it increased with the progression of disease. E-selectin serum level showed non-significant difference between benign and control groups. E-selectin gene was expressed in 76.1% in malignant tissues, in 44.0 % in benign tissues and in only one case in control group (6.2%). These results show highly significant difference between the diseased groups and the controls. The expression of E-selectin significantly correlated with aggressive tumor behavior. In conclusion, we found that the assessment of the adhesion molecule E-selectin in women with breast cancer can be added to the panel of tests that monitor the progress of the disease.
Keywords: Adhesion molecules, E-selectin, Breast Carcinoma, Tumor Grade, Prognosis, Molecular types, Gene expression.